NEGOTIATION AND POLITENESS STRATEGIES: PRAGMATIC FUNCTIONS OF THE SENTENCE-FINAL PARTICLE BA IN CHINESE TEXTBOOK DIALOGUES - Idris, Hatmi (Multikultura, 2026)
The sentence-final particle ba is frequently used in Chinese, yet its pragmatic functions in bargaining contexts remain challenging for second-language learners. This study investigates the use of ba in negotiation dialogues from the Hànyǔ Jiàochéng textbook series (Units 1 and 2), focusing on its role in maintaining politeness, protecting face, and facilitating agreement between interlocutors. Using a qualitative approach, each instance of ba was identified and analysed with reference to speech act theory, politeness principles, and the concept of face-threatening acts. The findings reveal that bastrengthens the speaker’s illocutionary force while mitigating potential discourtesy, reducing interactional tension, and providing interlocutors with space to accept or negotiate proposals. These functions help achieve successful bargaining outcomes. The study contributes to understanding pragmatic competence in Chinese as a foreign language and offers pedagogical insights for teaching sentence-final particles in negotiation contexts.